Modeling the dynamical behavior of the interaction of T-cells and human immunodeficiency virus with saturated incidence - Boulaaras S.; Jan R.; Khan A.; Allahem A.; Ahmad I.; Bahramand S. (Institute of Physics, 2025)
In the last forty years, the rise of HIV has undoubtedly become a major concern in the field of public health, imposing significant economic burdens on affected regions. Consequently, it becomes imperative to undertake comprehensive investigations into the mechanisms governing the dissemination of HIV within the human body. In this work, we have devised a mathematical model that elucidates the intricate interplay between CD4+ T-cells and viruses of HIV, employing the principles of fractional calculus. The production rate of CD4+ T-cells, like other immune cells depends on certain factors such as age, health status, and the presence of infections or diseases. Therefore, we incorporate a variable source term in the dynamics of HIV infection with a saturated incidence rate to enhance the precision of our findings. We introduce the fundamental concepts of fractional operators as a means of scrutinizing the proposed HIV model. To facilitate a deeper understanding of our system, we present an iterative scheme that elucidates the trajectories of the solution pathways of the system. We show the time series analysis of our model through numerical findings to conceptualize and understand the key factors of the system. In addition to this, we present the phase portrait and the oscillatory behavior of the system with the variation of different input parameters. This information can be utilized to predict the long-term behavior of the system, including whether it will converge to a steady state or exhibit periodic or chaotic oscillations. ? 2024 Institute of Theoretical Physics CAS, Chinese Physical Society and IOP Publishing.